Terjemahan TEKNIK TERJEMAHAN SUBTITLING TEMA SARKASME DALAM KOMEDI SITUASI “THE BIGBANG THEORY” - Kevin Hasudungan Sipahutar; Djauzi Ilmi; Misla Geubrina (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2024)
This research investigate the translation technique applied in the sarcasm, the process of applying the translation technique to the sarcasm, and finally to find which the most use translation technique. This research use the dialogue as the data from the film “The BigBang Theory” season 1 from episode 1-8 as the source of data. This research uses the theory of translation techniques as proposed by Molina & Albir (2002:509) there are 18 techniques proposed by Molina and Albir but in this research the researcher only uses five of the techniques. The method of this research is qualitative method. The findings of this research from the five techniques are adaptation with 30 times, literal translation with 36 times, discursive creation with 11 times, amplification with 5 times, and reduction with 14 times.